A complex interplay between the extracellular matrix and the innate immune response to microbial pathogens - Tomlin, Hannah; Piccinini, Anna M. (Wiley, 2018)
The role of the host extracellular matrix (ECM) in infection tends to be neglected. However, the complex interactions between invading pathogens, host tissues and immune cells occur in the context of the ECM. On the pathogen side, a variety of surface and secreted molecules, including microbial surface components recognizing adhesive matrix molecules and tissue‐degrading enzymes, are employed that interact with different ECM proteins to effectively establish an infection at specific sites. Microbial pathogens can also hijack or misuse host proteolytic systems to modify the ECM, evade immune responses or process biologically active molecules such as cell surface receptors and cytokines that direct cell behaviour and immune defence. On the host side, the ECM composition and three‐dimensional ultrastructure undergo significant modifications, which have a profound impact on the specific signals that the ECM conveys to immune cells at the forefront of infection. Unexpectedly, activated immune cells participate in the remodelling of the local ECM by synthesizing ECM glycoproteins, proteoglycans and collagen molecules. The close interplay between the ECM and the innate immune response to microbial pathogens ultimately affects the outcome of infection. This review explores and discusses recent data that implicate an active role for the ECM in the immune response to infection, encompassing antimicrobial activities, microbial recognition, macrophage activation, phagocytosis, leucocyte population balance, and transcriptional and post‐transcriptional regulation of inflammatory networks, and may foster novel antimicrobial approaches.